Pendederan Larva Ikan Gabus (Channa striata) di Kolam Terpal dengan Padat Tebar Berbeda - Hidayatullah, Syarif; Muslim, Muslim; Taqwa, Ferdinand Hukama (Jurnal Perikanan dan Kelautan, 2015)
Snakehead fish (Channa striata) is one of economically valued freshwater fish species, which is potential to be cultivated intensively. However, it has still mirred in the production because of low survival fry rate. The current research aimed to obtain the best stocking density on the survival and growth snakehead larvae rearing in plastic lined pond. Research was conducted in Batanghari Sembilan Fish Breeding Units from 3rd June until 3rd July 2014. This research used a completely randomized design with four treatments and three replications. The treatments were P1 (2 larvae per-litre), P2 (4 larvae per-litre), P3 (6 larvae per-litre), and P4 (8 larvae per-litre). The result showed that the difference of stocking density was significant on survival rate, length and weight growth. Stocking density P1 with 2 larvae per-litre was resulted the highest-value consist of survival rate (63.83 %), absolute length growth (3.61 cm), and-absolute weight growth (3.88 g). Water quality parameters during research in optimal range were temperature 27-32oC, pH 5.2-7.8, dissolved oxygen 2.08-7.06 mg.L-1, and ammonia concentration 0.006 - 0.072 mg.L-1.